A longitudinal study on the impact of species and age of animals on milk production in dairy animals - Chaudhary, J K; Verma, M R; Kshandakar, Shashank (Indian Journal of Dairy Science, 2020)
A longitudinal study was conducted to assess the impact of species and age of animals on milk production in dairy animals. The longitudinal data on milk yield of cattle and buffaloes have been recorded fortnightly interval up to 300 days for the period 2005 to 2014 from the dairy farm of Indian Veterinary Research Institute (IVRI), Izatnagar, Bareilly, Uttar Pradesh. From the study we found that the base line milk yield was significantly (p value